EVALUASI PERATURAN DAERAH KOTA PEKANBARU NOMOR 13 TAHUN 2001 TENTANG PENGATURAN USAHA INDUSTRI DI KOTA PEKANBARU (STUDI KASUS INDUSTRI BATU BATA PRESS DI KECAMATAN TENAYAN RAYA) - Sella Triadi Rahmadani; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Public policy is a product of government implementation processes and a model of choice of actions that will determine the fate of citizens. Regional Regulation No. 13 of 2001 concerning Regulating Industrial Business in the City of Pekanbaru is a policy product that must be carried out by the people of Pekanbaru City. The main concern of the research in this Regional Regulation is in Chapter XI Article 21 concerning types of industries subject to licensing and retribution, one of which is the brick industry in Tenayan Raya District. So far the Regional Regulation has not been implemented properly, because there are still many brick industry players who do not have business licenses. The purpose of this study is to find out the implementation and factors that hinder the Regional Regulations concerning Regulating Industrial Business. The theoretical concept used in Dunn's evaluation theory (Nugroho, 2017) is effectiveness, efficiency, adequacy, alignment, responsiveness and accuracy. This study uses a qualitative method of case study using purposive sampling and snowball sampling techniques with data collection techniques of observation, interviews, library research, and documentation. The results of this study indicate that the implementation of regional regulations regarding industrial business regulation is still not optimal, as evidenced by the large number of brick industries that do not have business licenses in accordance with the provisions in the regional regulations. It is recommended that the city government make changes to this regional regulation because the regional regulations regarding the regulation of industrial business are not in accordance with the higher regulations, in order to create an orderly brick industry that can improve the welfare of the community.Keywords: Evaluation, Regional Regulations, Industrial Business Regulations